Transferable skills of engineering students and lecturers at universities in Indonesia and Malaysia - Setiawan, A.; Bukit, M.; Kuntadi, I.; Yunos, J. M.; Salleh, K. M.; Sern, L. C.; Sulaiman, N. L.; Mohamad, M. F. (2017)
A transversal skill is one of the skills needed in every type of workplace setting. There is limited information about the perceptions of which transferable skills are needed in the workplace. The objective of this study is to explore the transferable skills among students and lecturers in TVET higher learning institutions in Indonesia and Malaysia. In the present study, transferable skills consist of communication skills, collaboration skills, problem-solving skills, entrepreneurship, and learning to learn skills. A qualitative research was conducted using survey. The five Likert scale questionnaire was distributed to lecturers and students from selected Malaysian and Indonesian universities who have bachelor program in engineering. Based on the analysis outcomes, it is clearly shown that Malaysian university engineering students yielded significantly higher scores on the perceptions of transferable skill acquisition in all measured components compared to their counterparts in Indonesia. Similar patterns of data distribution have been observed in Malaysian and Indonesian engineering students. Based on the lecturers’ perception, Malaysian and Indonesian Engineering Lecturers have comparable perceptions in the aspects of problem solving skills and entrepreneurship skills. In contrast, Malaysian university engineering lecturers gained significantly higher scores on the perception of communication skill, collaboration skill, and learning to learn skill compared to the Indonesian lecturers. The results indicate the need to increase transferable skills of both lecturers and students.